Project report and research on Online Event Management System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This project is an Event management portal that is implemented on a website. This project gives feature of remotely creating, removing, information retrieval, allotting tasks to different participants, etc in an event. This project is capable of providing all the important access to the admin and all the people related to a particular event. It gives Event Manager access to see participants and guest list. Also, he/she will be ableto create or delete an event. This project will reduce paperwork and manpower hence creating a hassle-free way of managing an event. Every even requirement will be traceable. One would be able to collect feedback from people and improve according to that feedback. Volunteer can be invited and duties can be assigned to them also revenue collection can be monitored through this platform. The purpose of creating this project is to digitalize the processes involved in an event, also it is easy to access so one can access it anytime and anywhere and perform a manage an event. It provides most of the basic functionality required by any event manager to smoothly run the event. This is to satisfy the needs of event manager as well as participants of event. They can enter their data and register for the event. This data is then sent to administrator which in turn can contact the participants.